Hepatoepithelioid hemangioendothelioma (HEHE): A comprehensive review of pathogenesis, characteristic features, diagnostic strategies and treatment approaches with the emphasis of surgical therapies - Serafin, Aleksandra; Suchołbiak, Aleksandra; Baran, Karolina; Podolak, Maja; Pachulska, Klaudia; Mikołajczyk, Oskar (Quality in Sport, 2025)
Introduction: Hepatoepithelioid hemangioendothelioma (HEHE) is a rare, low-grade malignant vascular tumor that can occur in multiple parts of the body but primarily affects the liver. It is marked by the presence of endothelial cells showing characteristics of both vascular and epithelial cells. The tumor typically appears as a vascularized tumor, displaying different levels of abnormal cell features. Despite developing and improving diagnostic methods, misdiagnosis remains a challenge due to its overlapping features with other tumors which primarily affect the liver. Aim of Study: This review aims to summarize current knowledge on the clinical and radiological manifestations, diagnostic challenges, and treatment managements of HEHE with a focus on surgical therapies and possible signs of recurrence. Materials and Methods: A comprehensive review of the literature on hepatoepithelioid hemangioendothelioma was performed using the PubMed database. Results and Conclusions: Hepatoepithelioid hemangioendothelioma progression is unpredictable, as both benign and malignant variants can occur. Due to its rarity and variability in both clinical and radiological presentation, accurate diagnosis of this tumor is challenging for clinicians. Currently, there is no universally accepted standard treatment protocol as a consequence of low prevalence of HEHE. Despite this, liver transplantation remains a therapeutic management of choice, particularly for patients with widespread or non-resectable disease. Nonetheless, long-term management is essential, involving regular monitoring, imaging studies, and liver function assessments to detect any signs of recurrence or emerging complications. More large-scale, long-term studies are needed to optimize management strategies for HEHE.